Autologous cytokine-induced killer cell transfusion increases overall survival in advanced pancreatic cancer. Issue 1 (December 2016) - Wang, Zibing; Liu, Yuqing; Li, Rui'e; Shang, Yiman; Zhang, Yong; Zhao, Lingdi; Li, Wei; Yang, Yonghao; Zhang, Xiaojie; Yang, Tiejun; Nie, Changfu; Han, Feng; et al.
Abstract Background Advanced pancreatic cancer (PC) has very poor prognosis with present treatments, thus necessitating continued efforts to find improved therapeutic approaches. Both preclinical and preliminary clinical data indicate that cytokine-induced killer (CIK) cells are an effective tool against various types of solid tumors. Here, we conducted a study to determine whether CIK cell-based therapy (CBT) can improve the outcomes of advanced PC. Methods Eighty-two patients with advanced PC, whose predicted survival time was longer than 3 months, were analyzed retrospectively. Of all the patients, 57 individuals were receiving chemotherapy, while the remaining 25 individuals were treated with CBT. Results The overall survival analysis was based on 48 deaths in the 57 patients in the chemotherapy group (84.2 %) and 18 deaths in the 25 patients in the CBT group (72.0 %). In the CBT group, the median overall survival time was 13.5 months, as compared to 6.6 months in the chemotherapy group (hazard ratio for death, 0.39; 95 % confidence interval, 0.23 to 0.65;p  < 0.001). The survival rate was 88.9 % in the CBT group versus 54.2 % in the chemotherapy group at 6 months, 61.1 % versus 12.5 % at 12 months, and 38.9 % versus 4.2 % at 18 months. The disease control rate was 68.0 % in the CBT group and 29.8 % in the chemotherapy group (p  < 0.001). Conclusions These results from this retrospective analysis appeared to imply that CBT might prolong survival in these high-risk PC patients. Prospective study is needed to corroborate this observation.